Large Amounts of Reactivated Virus in Tears Precedes Recurrent Herpes Stromal Keratitis in Stressed Rabbits Latently Infected with Herpes Simplex Virus. (3rd March 2016) - Perng, Guey-Chuen; Osorio, Nelson; Jiang, Xianzhi; Geertsema, Roger; Hsiang, Chinhui; Brown, Don; BenMohamed, Lbachir; Wechsler, Steven L.
Abstract: Aim : Recurrent herpetic stromal keratitis (rHSK), due to an immune response to reactivation of herpes simplex virus (HSV-1), can cause corneal blindness. The development of therapeutic interventions such as drugs and vaccines to decrease rHSK have been hampered by the lack of a small and reliable animal model in which rHSK occurs at a high frequency during HSV-1 latency. The aim of this study is to develop a rabbit model of rHSK in which stress from elevated temperatures increases the frequency of HSV-1 reactivations and rHSK. Materials and methods : Rabbits latently infected with HSV-1 were subjected to elevated temperatures and the frequency of viral reactivations and rHSK were determined. Results : In an experiment in which rabbits latently infected with HSV-1 were subjected to ill-defined stress as a result of failure of the vivarium air conditioning system, reactivation of HSV-1 occurred at over twice the normal frequency. In addition, 60% of eyes developed severe rHSK compared to <1% of eyes normally. All episodes of rHSK were preceded four to five days prior by an unusually large amount of reactivated virus in the tears of that eye and whenever this unusually large amount of reactivated virus was detected in tears, rHSK always appeared 4–5 days later. In subsequent experiments using well defined heat stress the reactivation frequency was similarly increased, but no eyes developed rHSK. Conclusions : The results reported here support the hypothesis that rHSK is associated not simply with elevated reactivation frequency, but rather with rare episodes of very high levels of reactivated virus in tears 4–5 days earlier.